2014
DOI: 10.1063/1.4903887
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-thick flat lens with adjustable focus

Abstract: We report laser beam focusing by a flat, homogeneous film with a thickness of less than 100 nm. The effect relies on refractive index changes occurring in vanadium dioxide as it undergoes a phase transition from insulator to metal. Phase front curvature is achieved by means of temperature gradients, and adjustable focal lengths from infinity to 30 cm are attained. V C 2014 AIP Publishing LLC. [http://dx.doi.org/10.1063/1.4903887] Thin flat lenses have found applications in areas such as integrated optics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Several studies have reported the effects of a global, thermally, or optically driven phase transition in VO 2 on the plasmonic response of nanoparticles and metamaterials over a broad spectral range from terahertz, mid-infrared, , and near-infrared to visible. In the visible and near-infrared, studies of plasmonic effects on the optical excitation of the IMT have focused on hot-electron injection-driven ultrafast processes , and on nonresonant, continuous-wavemediated plasmonic heating, , including our demonstration of picosecond control of switching …”
mentioning
confidence: 99%
“…Several studies have reported the effects of a global, thermally, or optically driven phase transition in VO 2 on the plasmonic response of nanoparticles and metamaterials over a broad spectral range from terahertz, mid-infrared, , and near-infrared to visible. In the visible and near-infrared, studies of plasmonic effects on the optical excitation of the IMT have focused on hot-electron injection-driven ultrafast processes , and on nonresonant, continuous-wavemediated plasmonic heating, , including our demonstration of picosecond control of switching …”
mentioning
confidence: 99%
“…This phase shift, along with the field amplitudes, determine the polarization state of reflected and transmitted light beams. For example, with Δ = ± π or Δ = ± π/2, linearly polarized light may rotate by up to 90 o , or be switched between linear and circular states [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in optical properties have been useful mostly for applications of spectral filtering and fieldamplitude modulation of infrared light, but recently, applications have also been found for phase and polarization modulation of visible and infrared light [6][7][8][9][10]. Phase and polarization modulations rely on the principle that in a material with complex-valued refractive indices like VO 2 , optical phase shifts are generally unequal in s-and p-polarizations.…”
Section: Introductionmentioning
confidence: 99%